Cell wall composition in Cryptococcus neoformans is media dependent and alters host response, inducing protective immunity - Upadhya, Rajendra; Lam, Woei C.; Hole, Camaron R.; Vasselli, Joseph G.; Lodge, Jennifer K. (Frontiers in Fungal Biology, 2023)
Cryptococcus neoformans is a basidiomycetes fungus and can cause meningoencephalitis especially in immunocompromised patients. Cryptococcus can be grown in many different media, although little attention has been paid to role of growth conditions on cryptococcal cell wall or on virulence. Two commonly used media to grow Cryptococcus before being used in in vitro or in vivo experiments are Yeast extract, Peptone and Dextrose (YPD), or Yeast Nitrogen Base (YNB). We observed that the growth of wild type C. neoformans KN99 significantly changes the pH of unbuffered media during growth. It raises the pH to 8.0 when grown in unbuffered YPD, but lowers the pH to 2.0 when grown in unbuffered YNB (YNB-U). Importantly, the cell wall composition was substantially impacted by growth in different media. Cells grown in YNB-U had a 90% reduction in chitosan, the deacetylated form of chitin, compared to cells grown in YPD. The decrease in pH and chitosan in the YNB-U grown cells was associated with a significant increase in some Pathogen-Associated Molecular Patterns on the surface of cells compared to the cells grown in YPD or YNB, pH 7. This altered cell wall architecture resulted in a significant reduction in virulence when tested using a murine model of infection. Furthermore, when heat-killed cells were used as the inoculum, KN99 grown in YNB-U caused an aberrant hyper-inflammatory response in the lungs, resulting in rapid animal death. On the contrary, heat-killed KN99 cells grown in YNB, pH 7 caused little to no inflammatory response in the host lung, but when used as a vaccine, they conferred a robust protective response against a subsequent challenge infection with the virulent KN99 cells. These findings emphasize the importance of culture media and pH during growth in shaping the content and organization of the C. neoformans cell wall, as well as their impact on fungal virulence and the host response.